ANALISIS KELAYAKAN USAHA BROILER DI PETERNAKAN MAHMUDDIN DESA TATAKAN KECAMATAN TAPIN SELATAN KABUPATEN TAPIN - Muhammad Rifqi; Herliani Herliani; Danang Biyatmoko (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
This research was conducted at Mr. Mahmuddin's broiler farm located in Tatakan Village, South Tapin District, Tapin Regency. The research began in January to May of 2024. This research aims to study the income level of broiler chicken business with a partnership pattern and to determine the feasibility of broiler chicken business with a partnership pattern on Mahmuddin Farm in Tatakan Village, South Tapin District, Tapin Regency. The components used in evaluating business feasibility include production costs, revenue, and business income obtained from broiler farming. Parameters measured are using cost benefit analysis indicators which include: R/C Ratio, B/C Ratio, BEP, and Performance Index (IP) parameters. The results showed that the feasibility analysis of a broiler livestock business with a business scale of 41,165 heads for four periods was profitable as an agribusiness-oriented business where the profit earned was Rp. 60,996,439 in four periods, and feasible to develop with a value of R / C ratio of 1,06 and B / C ratio of 0.06. BEP analysis shows that the amount of production is higher than the production BEP value (Production>BEP Production) which is 58,195.01 kg for 4 periods and the price BEP is still lower than the set at Rp. 23,408-/kg so that it has met the empirical standards in the break-even analysis calculation. As for the assessment using the Performance Index (IP) parameter in the first period is 547, second 269, third 550, and in the last period 888. This shows that Mr. Mahmuddin's broiler farm business located in Tatakan Village, South Tapin District, Tapin Regency is feasible to continue or develop.